2006
DOI: 10.1186/1472-6920-6-32
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a radiation safety training intervention for oncology nurses: a pretest – intervention – posttest study

Abstract: BackgroundRadiation, for either diagnosis or treatment, is used extensively in the field of oncology. An understanding of oncology radiation safety principles and how to apply them in practice is critical for nursing practice. Misconceptions about radiation are common, resulting in undue fears and concerns that may negatively impact patient care. Effectively educating nurses to help overcome these misconceptions is a challenge. Historically, radiation safety training programs for oncology nurses have been comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
(5 reference statements)
2
15
0
1
Order By: Relevance
“…11 Dauer et al had also similar findings regarding training intervention among nurses on radiation safety. 12 Training efficacy as evident in the current study had also been emphasized by Muthén and Curran (1997). 13 Similar findings were also there in studies by Dauar LT from New York City and also from a school-based study from Saudi Arabia.…”
Section: Discussionsupporting
confidence: 80%
“…11 Dauer et al had also similar findings regarding training intervention among nurses on radiation safety. 12 Training efficacy as evident in the current study had also been emphasized by Muthén and Curran (1997). 13 Similar findings were also there in studies by Dauar LT from New York City and also from a school-based study from Saudi Arabia.…”
Section: Discussionsupporting
confidence: 80%
“…Table 4 shows the percentage of correct answers given for each question, before and after the Endocrine Circuit application. Students' scores for questions 3,4,6,7,8,9, and 10 improved after the contact with the Endocrine Circuit. The greatest improvements, considering a higher percentage of correct answers after Endocrine Circuit application, were observed for questions 3 (36%), 4 (29%), 8 (29%), and 9 (42%).…”
Section: Resultsmentioning
confidence: 98%
“…The percentage of correct answers in the questionnaire increased from 64 to 85.2% when comparing the pretest and posttest, an increase of 21.2%. The pretest-posttest design is widely used to test the effectiveness of educational approaches in the scientific literature (3,4), which gives us confidence in the adequacy of our conclusions. Analyzing individually each question, seven questions showed improve- On top of good performance, the Endocrine Circuit activity was also well received by the students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that radiation safety education improved compliance with radiation safety procedures in medical staff who participated in interventional procedures, reducing their exposure to radiation (Alahmari & Sun, ; Sheyn et al., ), and that nurses’ knowledge of and attitudes towards radiation safety can be enhanced through safety education (Dauer, Kelvin, Horan, & Germain, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that radiation safety education improved compliance with radiation safety procedures in medical staff who participated in interventional procedures, reducing their exposure to radiation (Alahmari & Sun, 2015;Sheyn et al, 2008), and that nurses' knowledge of and attitudes towards radiation safety can be enhanced through safety education (Dauer, Kelvin, Horan, & Germain, 2006). Therefore, the ICRP and other concerned academic institutions recommend safety education for medical workers to control radiation safely (Chen, 2014;ICRP, 2009;Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%